Influence of mineral fertilizers on economic indicators of cultivated varieties of spring triticale in the conditions of the republic of Mari El - Maksimov V. A. (EDP Sciences, 2021)
In modern socio-economic conditions, the production of high-quality grain remains the main task of agricultural production. The main way to solve it is to increase productivity by introducing new varieties and crops with high potential and improving the cultivation technology with minimal costs. Agrarians of the North-East of the Non-Chernozem Zone of Russia, having in their land, use poorly fertile sod-podzolic soils of varying degrees of cultivation. To increase the productivity of grain crops, they use adapted resource-saving technologies, in which the level of mineral fertilizer is determined by the magnitude of the dose of the nutrient established experimentally. The high productivity of the variety, along with the quality of the grain, is the most important indicator of the ultimate goal of every breeder. To assess the economic efficiency of the cultivation of spring triticale, studies were carried out on nine varieties: Saur, Dobroe, Zaozerye, KNIISH 9, KNIISH 11, KNIISH 22, Savva, Timur, Rovnya. The results of our studies convincingly indicate that in the conditions of the republic, even against an unfertilized background, cultivated varieties of spring triticale, provide grain yield from 2.5 to 3.8 t/ha. Some of the most important economic indicators characterizing production efficiency are such indicators as the cost of production and the degree of efficiency of grain production, expressed by the level of profitability. The main application of mineral fertilizers (N60P60K60, (P60K60) and the introduction of nitrogen fertilization in tillering at a dose of N30 increases the cost of 1 kg of grain by 5-8%, thereby reducing the profitability of production when cultivating varieties. The cultivation of varieties Rovnya, Zaur, Zaozerye, KNIISH 22, KNIISH 11, Timur was economically profitable, but less profitable than varieties KNIISH 9, Dobroe and Savva. The cost of production of a kilogram of grain was on the option without mineral nutrition from 5.1; 7.0; 5.9; 5.1; 4.8; and 6.4 rubles, respectively. On fertilized options, the cost decreased to a minimum of 4.1 rubles in the Timur variety with the main application of N60P60K60 with nitrogen fertilization N30 during tillering. The maximum increase in the cost price was shown by the varieties Timur, Zaozerye: 4.8 and 4.9 rubles against the background of the main application of N60P60K60. On average for 2020 according to the results of economic analysis, the lowest cost price and the highest level of profitability indicator are observed when cultivating varieties KNIISH 9, Dobroe and Savva at all levels of mineral nutrition.